Efficient Market Hypothesis: Foreign Exchange Market of Bangladesh - Firoj, Mahamuda; Khanom, Sharmina (International Journal of Economics and Financial Issues, 2018)
Efficiency in a foreign exchange market (FEM) is very essential for a developing economy like Bangladesh as the foreign exchange rates play a critical role to determine the various macroeconomic policies and issues of an economy. Thus the main objective of this paper is to investigate the efficiency of the FEM of Bangladesh. Statistics that have worn in this paper comprises of nominal daily exchange rates (spot) of seven bilateral currency rates in opposition to the Bangladeshi currency Taka over the period 1st January 2010 to 30th November 2017 obtained from the website of Bangladesh Bank. The unit root test and the cointegration test are run by econometric software to look into the efficiency of the FEM of Bangladesh. The concluding findings indicate that all the seven exchange rates succeed the random walk hypothesis and this is the verification of the weak form of efficiency. Moreover, the cointegration scrutiny depicts there is no indication of the semi-strong form of efficiency in the FEM of Bangladesh. Keywords: Foreign Exchange Market, Exchange Rate, Efficiency. JEL Classifications: F31, E44 DOI: https://doi.org/10.32479/ijefi.7097